2021
DOI: 10.1073/pnas.2014783118
|View full text |Cite
|
Sign up to set email alerts
|

Human retroviral antisense mRNAs are retained in the nuclei of infected cells for viral persistence

Abstract: Human retroviruses, including human T cell leukemia virus type 1 (HTLV-1) and HIV type 1 (HIV-1), encode an antisense gene in the negative strand of the provirus. Besides coding for proteins, the messenger RNAs (mRNAs) of retroviral antisense genes have also been found to regulate transcription directly. Thus, it has been proposed that retroviruses likely localize their antisense mRNAs to the nucleus in order to regulate nuclear events; however, this opposes the coding function of retroviral antisense mRNAs th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 65 publications
1
30
0
Order By: Relevance
“…Interestingly, studies combining predictions with experimental validation in a large patient cohort ( n = 432) showed that despite Tax being the immunodominant protein, CD8 + T-cells specific to the antisense protein HTLV-1 basic leucine zipper (HBZ) are the most effective CD8 + T-cells [ 54 ]. However, antigen presentation of HBZ is impaired, possibly due to nuclear retention of HBZ [ 55 , 56 ]. Thus, latency reversal may also be achieved by enhancing antigen presentation of HBZ, a topic that is very interesting, but not discussed within this review.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, studies combining predictions with experimental validation in a large patient cohort ( n = 432) showed that despite Tax being the immunodominant protein, CD8 + T-cells specific to the antisense protein HTLV-1 basic leucine zipper (HBZ) are the most effective CD8 + T-cells [ 54 ]. However, antigen presentation of HBZ is impaired, possibly due to nuclear retention of HBZ [ 55 , 56 ]. Thus, latency reversal may also be achieved by enhancing antigen presentation of HBZ, a topic that is very interesting, but not discussed within this review.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reveal that the 3′LTR serves as the 5′LTR in the DNA negative strand, and transcribes an antisense ncRNA named ASP (the ncRNA codes the antisense protein ASP) [ 84 , 85 ]. The ASP regulates the HIV latency by RNA:DNA base pairing to 5′LTR with Watson–Crick and Hoogsteen specificity.…”
Section: Hiv Ltrsmentioning
confidence: 99%
“…When HBZ is expressed by its native promoter, the 3 ′ LTR, HBZ mRNA is mainly present in the nucleus, but it resides in the cytoplasm when expressed by the exogenous strong promoter. The difference between the HBZ mRNAs in these two scenarios is the length of the poly A tail: poor polyadenylation is the cause of the nuclear localization of HBZ mRNA (48). HBZ mRNA expressed by the 3 ′ LTR can promote the proliferation of T cells, whereas HBZ mRNA expressed by a strong promoter did not promote T-cell proliferation, indicating that nuclear localization is involved in this function.…”
Section: Function Of Hbzmentioning
confidence: 99%